2017
DOI: 10.1515/jppr-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of viruses infecting cucurbits and determination of genetic diversity of Cucumber mosaic virus in Lorestan province, Iran

Abstract: Various viral pathogens infect Cucurbitaceae and cause economic losses. Th e aim of the present study was to detect plant viral pathogens including Cucumber mosaic virus (CMV), Cucumber green mottle mosaic virus (CGMMV), Zucchini yellow mosaic virus (ZYMV), Cucurbit yellow stunting disorder virus (CYSDV) and Cucurbit chlorotic yellows virus (CCYV) in Lorestan province, in western Iran, and also to determine CMV genetic diversity in Iranian populations. A total of 569 symptomatic leaf samples were collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, the Nigerian population was unique, as the frequency of purifying selection within the RNA1 sequences was less than half the rates within the general subgroup IB, while the CP gene fragments revealed very a high number of negative selections comparable to subgroups IA, IB and II. The occurrence of negative selection within the CMV CP gene has been previously reported (Liu et al, 2009;Nouri et al, 2014;Hasanvand and Shams-Bakhsh, 2017). However, the properties within the Nigerian population could be due to the widespread occurrence of the virus across several hosts, driven by multiple introductions and independent coevolution across various spatial and temporal scales.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the Nigerian population was unique, as the frequency of purifying selection within the RNA1 sequences was less than half the rates within the general subgroup IB, while the CP gene fragments revealed very a high number of negative selections comparable to subgroups IA, IB and II. The occurrence of negative selection within the CMV CP gene has been previously reported (Liu et al, 2009;Nouri et al, 2014;Hasanvand and Shams-Bakhsh, 2017). However, the properties within the Nigerian population could be due to the widespread occurrence of the virus across several hosts, driven by multiple introductions and independent coevolution across various spatial and temporal scales.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, the presence of more CMV isolates belonging to subgroup IB has now been confirmed in Nigeria and appears to be more prevalent, especially across different agro-ecologies and hosts. The strain is reported to have Asian origins ( Roossinck, 2002 ; Hasanvand and Shams-Bakhsh, 2017 ), and its expansion into Africa points to the looming threat the virus poses to food security, especially for the continent’s most populous country. CMV isolates belonging to subgroup IB have been found to occur in East Africa ( Kidanemariam et al, 2019 ), and this report confirms its expansion into West Africa and probably beyond.…”
Section: Discussionmentioning
confidence: 99%
“…absorbance value at 405 nm wavelength in both the year are presented in Table 4 and the overall results thus revealed that expect for the samples from Dasher II and Poinsett all other screened lines were found infected with cucumber mosaic virus and showed positive reaction (presence of yellow color) with CMV specific antibody as the O.D values were more than twice the value of negative control reaction. Shetti et al (2012), Suresh et al (2013) and Hasan and Shams-bakhsh (2017) Table 5. Disease reaction of cucumber germplasm against cucumber mosaic disease under field conditions (2019 and 2020) CONCLUSION Out of forty germplasm/lines of cucumber screened against cucumber mosaic disease during 2019 and 2020 only two germplasm ., Dasher II and Poinsett were found viz resistant whereas CS-13, CS-16, CS-51, CS-54, Fumiko-10 and Don-1 were moderately resistant.…”
Section: Sativusmentioning
confidence: 99%